ANALISIS MINAT BACA PENGUNJUNG PERPUSTAKAAN DAERAH KABUPATEN ASAHAN DENGAN PENDEKATAN DATA MINING MENGGUNAKAN METODE K-MEANS - Sulistiawan, Defry Nazhira; Saputra, Herman; Sena, Maulana Dwi (LPPM STMIK Royal Kisaran, 2024)
Abstract: Asahan District Library Service is a growing regional public library and is always making improvements, improvements, and trying to maintain the quality of its services. This is evidenced by the provision of services such as borrowing and returning books (circulation), and adding to the book collection every year. Knowing and understanding visitors' reading interests is the main key in improving the quality of library services. However, managing reading interest from various levels of society is not an easy task. Each individual has different reading preferences and interests. Therefore, a systematic and efficient approach is needed in identifying reading interests to be able to manage the addition of book collections. Currently, in the process of adding a book collection, the library only makes employee recommendations, and the latest books, as a reference in increasing the number of book collections, without considering which books are most in demand to increase the collection. This can have a negative impact if there is an addition to the collection of books that are not in demand to read, which can cause problems in terms of service and finance. Based on this, the application of data mining, especially the K-Means method, will be carried out, to support the management of book collection additions, by grouping the reading interests of library visitors who have the same identity, so that libraries are more precise in managing book collections in grouping books that are rarely borrowed, often borrowed and very often borrowed. Keywords: visitor reading interest; k-means method; library; data mining; book collectionAbstrak: Dinas Perpustakaan Kabupaten Asahan merupakan perpustakaan umum daerah sedang berkembang dan terus memperbaiki, membenahi, dan meningkatkan layanan. Diberikannya layanan seperti pinjaman dan sirkulasi, dan penambahan koleksi buku setiap tahunnya. Mengetahui dan memahami minat baca pengunjung menjadi kunci utama dalam meningkatkan kualitas layanan perpustakaan. Namun, mengelola minat baca dari berbagai lapisan masyarakat bukanlah tugas yang mudah. Setiap individu memiliki preferensi dan minat baca yang berbeda-beda. Oleh karena itu, diperlukan suatu pendekatan yang sistematis dan efisien dalam mengidentifikasi minat baca untuk dapat mengelola penambahan koleksi buku. Saat ini, ketika perpustakaan meningkatkan koleksi bukunya, mereka hanya bergantung pada rekomendasi karyawan dan buku terkini untuk menambah jumlah buku. Mereka tidak mempertimbangkan buku mana yang paling diminati untuk menambah koleksi mereka. Hal ini dapat berdampak negatif jika terdapat penambahan koleksi buku yang kurang diminati untuk dibaca, yang dapat menimbulkan masalah dari sisi pelayanan maupun finansial. Berdasarkan hal tersebut maka akan dilakukan penerapan data mining khususnya metode K-Means, untuk mendukung pengelolaan penambahan koleksi buku, dengan cara mengelompokkan minat baca pengunjung perpustakaan yang memiliki kesamaan identitas, sehingga perpustakaan lebih tepat dalam mengelola koleksi buku dalam mengelompokan buku yang jarang dipinjam, sering dipinjam dan sangat sering dipinjam.Kata Kunci: minat baca pengunjung; metode k-means; perpustakaan; data mining; koleksi buku